The spine crasher: a challenging diagnosis - Anuar, Muhamad Azamin; Shaban Mohamed, Mossad Abdelhak; Mohd Azhar, Nur Syuhada; Abu Bakar, Asrar; Hasan, Taufiq Hidayat (2019)
Spinal tuberculosis in children is an established preventable disease in developing countries. Complications are devastating due to its aptitude to cause bone destruction, spinal deformity and paraplegia. We present an eight-month old girl with isolated gross motor regression and evolving spastic paraplegia. It highlights the challenge we encountered due to delay in garnering the pertinent investigation.